PENGENDALIAN KUALITAS PROSES PRODUKSI KAYU OLAHAN TURNING DENGAN MENGGUNAKAN METODE SEVEN TOOLS DI CV. GAVRA PERKASA - Sofinurriyanti Sofinurriyanti; Hikmatul Maulida (Bina Teknika, 2018)
This study aims to determine the quality of products in CV. Cavra Perkasa and to reduce product defects in CV. Garva Perkasa at the time of production. CV. Gavra Perkasa is a company engaged in the industry of building goods made of wood. The products produced are wood flooring, woodwork for building materials (E4E / E2E), handrails, staircases (turning), door frames, and floors with decking. There are seven main quality control tools that can be used as a tool to control quality, among others: check sheet, histogram, control chart, pareto diagram, causal diagram, scatter diagram and various processes. There are three types of damage that occur in turning processed wood products namely Monocular / Perforated, Middle Broken, and Moldy damage. The biggest damage is the edged / perforated damage with a total damage percentage of 47.19%, the disability of wood products in the middle rupture is 30.55% and the lowest value of disability results is 22.24%. So that the total percentage of damage is 13481.